Knowledge, attitude, lifestyle practice and factors affecting behaviour modifications in relation to metabolic syndrome among type 2 diabetes patients attending diabetes clinic HUSM, Kelantan - Yaacob, Nasibah Tuan (2018)
INTRODUCTION: Metabolic syndrome has become a major public health concern worldwide and in Malaysia as it imposes an enormous health risk. The prevalence of metabolic syndrome in Malaysia is high compared to other Asian countries. OBJECTIVES: The objectives of the study are to determine knowledge, attitude, lifestyle practices and factors affecting behaviour modifications (including sociodemographic characteristics, body mass index and clinical characteristics such as having metabolic syndrome, body weight perception mismatched, body weight satisfaction, perception of body weight as health problem, perception of body weight disturbing daily activities, knowledge and attitude and ever heard of metabolic syndrome) in relation to metabolic syndrome among diabetes patients attending diabetes clinic Hospital Universiti Sains Malaysia, Kelantan. METHODOLOGY: Cross sectional study was conducted from June until November 2017 among diabetes patients attending diabetes clinic Hospital Universiti Sains Malaysia, Kelantan. The study used a self-administered questionnaire. Patient’s physical paramaters including weight, height and waist circumference was recorded, while thebiochemical parameters were retrieved from the patient’s folder and laboratory information system. RESULTS: There were 255 diabetes patients involved. Most of the participants have good knowledge (97.3%) and positive attitude (99.2%). The mean (SD) score for knowledge, attitude and behaviour changes were 91.1% (6.26) and 94.5% (8.09) respectively. For lifestyle practices, most of the respondents have inadequate physical activities as 91.8% had sedentary and low physical activities. Dietary components show inadequacy in term of vegetables, fruit intake and imbalance used of fat among respondents. Only 66.3% of the respondents took vegetables and 49.0% took fruits regularly. There is low intake of low fat milk as 22.4% drink milk regularly. 56.9% of them never used corn oil for cooking and 66.7% used palm oil regularly. There were four significant associated factors for behaviour modifications namely female sex (p: 0.017), having secondary (p: 0.006) and tertiary education (p: 0.041). Having a positive weight perception did not disturbed ADL also associated with positive behavioural changes among diabetes patients (p: 0.010). CONCLUSION: Despite high percentage of knowledgeand attitude, it does not associate with positive behaviour changes. Behaviour changes in chronic disease is a complex process as it often affected by many other factors including social responsibility, time limitation and occupation.